Effect of Virtual Reality-Based Instruction on Student Learning Outcomes: An Experimental Study in Higher Education in Oman - M. Ghazal, Taher (Journal of Soft Computing and Data Mining, 2026)
Traditional university instruction is predominantly lecture-based, often limiting student interaction and experiential learning opportunities. This study investigates the impact of virtual reality (VR)-based instruction on selected learning outcomes among undergraduate students at Sohar University, Oman. A mixed-methods experimental design was employed, involving 80 students recruited through convenience sampling and randomly assigned to control and experimental groups (n = 40 each). Pre- and post-intervention assessments were conducted to measure academic performance and engagement. Quantitative analysis included paired-samples t-tests to evaluate within-group learning gains, independent-samples t-tests to compare post-test differences, and linear regression to examine the predictive effect of VR exposure while controlling for baseline performance. Assumptions of normality (Shapiro–Wilk W = 0.97, p = 0.18), homogeneity of variance (Levene’s F = 1.26, p = 0.26), and independence were satisfied. Results indicate that the experimental group achieved higher post-test scores (M = 82.4, SD = 6.8) compared to the control group (M = 71.3, SD = 7.5), with a significant mean difference of 11.1 (95% CI [5.2, 17.0]; t(78) = 3.67, p < 0.001; Cohen’s d = 0.82). Qualitative data from purposively sampled focus groups (n = 12) were analyzed using thematic analysis with established reliability (Cohen’s ? = 0.81) and integrated through triangulation to support quantitative findings. The results indicate that VR-based instruction is associated with improved performance and engagement within the studied cohort; however, inference is bounded to the institutional context, warranting further multi-site validation.